Incidence and determinant of eclampsia and its associated complication in tertiary care hospital of Gujarat, India - Banker, Chirag; Mehta, Latika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is one of common cause of maternal mortality in developing country like India. It can be detected and prevented if early ANC care is properly done. Mainstay of management in case of eclampsia is early delivery to improve the prognosis in terms of reducing maternal and perinatal morbidity and mortality. Methods: This prospective study was carried out in the department of obstetrics and gynaecology, at tertiary care centre in the state of Gujarat, for a period of two years from July 2012 to June 2014. With purposive sampling method all patients admitted with complain of eclampsia is included in study. Details are taken in predesigned, pre-validated and prescribed proforma. Results: Hospital based incidence of eclampsia in our study is 1.11%. Majority of the patient were unbooked. Eclampsia is a disease of young primigravida, specifically teenage primigravida. Seventy-five percentage of eclampsia cases occurred in the antenatal period, 14% in intranatal period and 11% in the postnatal period. Conclusions: In developing countries like India still eclampsia is major problem. Good antenatal care with increased antenatal visits may help in reducing the incidence. Increased incidence among young primigravida and low socio-economic status group provides the target group for medical measures.